Association of IRS1 (Gly972Arg) and IRS2 (Gly1057Asp) genes polymorphisms with OSA and NAFLD in Asian Indians. - Surya Prakash Bhatt (Public Library of Science (PLoS), 2021)
Aim and objective The aim of the study was to investigate the relationships between insulin receptor substrate (IRS) 1 (Gly972Arg) and IRS2 (Gly1057Asp) genes with obstructive sleep apnea (OSA) and non-alcoholic fatty liver disease (NAFLD) in Asian Indians. Method A total of 410 overweight/obese subjects (130 with OSA with NAFLD, 100 with OSA without NAFLD, 95 without OSA and with NAFLD and 85 without OSA and without NAFLD) were recruited. Degree of NAFLD was based on liver ultrasound and of OSA on overnight polysomnography. Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism and confirmed by gene sequencing. Result Mean values of blood pressure, body fat markers, blood glucose, lipids, liver function, and markers of insulin resistance were significantly increased in OSA and NAFLD subjects (p<0.05). In addition, according to age (years) categories, blood pressure, blood glucose, lipids, obesity markers, and markers of insulin resistance were significantly higher in 45-60 years group as compared to 20-45 years group (p<0.05). In IRS1 gene, the genotype frequency (%) of Arg/Arg was significantly higher in NAFLD and OSA subjects. In addition, Gly/Arg genotype of IRS1 gene was associated with significantly higher body mass index, fat mass, %body fat, triglycerides, cholesterol, alkaline phosphate, aspartate transaminase, fasting insulin and HOMA-IR levels in OSA and NAFLD subjects. No significant difference in genotype frequencies of IRS2 was observed between four groups. Further we found that subjects carrying IRS1 Gly/Arg (OR 4.49, 95% C.I. 1.06-12.52, p = 0.002) genotype possess a much higher risk of OSA and NAFLD compared to IRS2 Gly/Asp (OR 1.01, 95% C.I. 0.8-2.56, p = 0.05). In sub group analysis of IRS1 Gly/Arg have significant differences between the mild, moderate and severe group (P<0.05). In addition, patients with the 'Gly' allele were inclined to develop more severe OSA. Conclusion We concluded that Asian Indian subject carrying the allele Gly972Arg polymorphism of IRS1 is predisposed to develop OSA and NAFLD.